Relationships between learning difficulties and psychological problems in preadolescent children from a longitudinal sample. - Prior, Margot; Smart, Diana; Sanson, Ann (Journal of the American Academy of Child & Adolescent Psychiatry, 1999)
A study was conducted to investigate the relationship between learning and behavior problems in preadolescent children and to examine associations between DSM-diagnosed disorders and types of learning difficulties using clinical and comparison groups of 11- to 12-year-old children. Findings indicated that children in the clinical group were disadvantaged on all learning and behavioral indices and that their problems in many cases had been evident from seven to eight years of age. Specific associations between types of learning difficulties and both internalizing and externalizing disorders emerged. Numeracy difficulties were strongly related to DSM diagnoses for boys and girls, and externalizing problems were inclined to co-occur with a mixture of learning difficulties.